COMPREHENSIVE MODEL FOR UNDERSTANDING AND ENHANCING PRO- ENVIRONMENTAL PURCHASE BEHAVIOR: TOWARDS A CONCEPTUAL FRAMEWORK - Achchuthan, S.; Umanakenan, R.; Kajenthiran, K. (University of Jaffna, 2017)
Inculcating pro-environmental purchase behavior is beneficial to both individuals and the society at large. The TPB has been generally applied to understand and examine pro-environmental purchase behavior. However, as the underpinnings of this theory are not adequate to understand the entire process of the development of pro-environmental purchase behavior, a more comprehensive theoretical framework is required. Combining the TPB with the VBN Theory provides such a comprehensive theoretical framework. Moreover, the presented model incorporates green perceived value and green Skepticism to predict pro–environmental purchase behavior strongly and to tackle the puzzle like green marketing myopia meticulously. It suggests that pro – environmental purchase behavior may be strongly predicted by pro- environmental purchase intention, green perceived value and green skepticism. The implications of this framework for theory and practice are discussed, as directions for future research, which would be of use to researchers and practitioners in the societal marketing field.
Keywords: Pro- Environmental Purchase Behavior; Value- Belief- Norm Theory; Theory of Planned Behavior